Sustainable transportation in the taxi industry in Johannesburg: The opportunities, challenges, and solutions towards achieving sustainable transport - Wakelin-Theron, Nicola; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2023)
The taxi industry provides mobility and employment. Sustainable transportation must be served by innovative practices, namely new mobility types, appropriate infrastructure, and intelligent systems to manage livable environments. This study aims to determine the current practices and sustainable alternatives for taxi role players and the Department of Transport. The objectives were to determine probable future changes as well as ascertain whether there is a gap between the future of transportation and the vision of stakeholders. A qualitative research approach using semi-structured individual interviews was adopted. Participants for the study were selected purposively in Johannesburg and included people working in the industry as well as experts in the field. The findings highlighted a significant gap between the understanding of the South African National Taxi Council, Department of Transport, taxi owners, taxi marshals, and taxi drivers regarding the way forward towards embracing sustainable practices. The researchers conclude that sustainable innovations are imperative for transportation development, economic growth, as well as reaching the United Nations sustainable development goals. This study provides a good understanding of the backgrounds unique to taxi industry in Johannesburg, sustainable mobility practices, as well as gaps in the industry